Laparoscopic pyeloplasty of the pyeloureteral segment: our experience - A. S. Al-Shukri; Ju. A. Ponomareva; S. A. Reva; R. M. Ammo; S. V. Kostuykov; S. B. Petrov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the study was to analyze the results and to introduce our experience of the laparoscopic pyeloplasty regarding the stricture of the pyeloureteral segment.METHODS and MATERIALS. Our study represents results of treatment of 114 patients who had surgical treatment during the years 2013–2018. In that period, we made 114 primaries and 9 secondaries laparoscopic pyeloplasties with transperitoneal access. In this account, there were 43 men aged from 19 to 64 years, average age was (34.9±3.7), and 71 women aged from 19 to 77 years, average age was (39.2±4.2). All patients underwent ultrasound examination of the kidneys on the day of discharge and 3-5 days after stent extraction. Control examination, which included history taking, examination, clinical and biochemical blood analyses, clinical urine analysis and ultrasound of the kidneys were performed after 3 months. Plain and excretory urography were performed 6 and 18 months after surgical intervention. RESULTS. Operative removal of the stricture of the pyeloureteral segment was successful in 105 (92.2 %) out of 114 cases. 9 patients (7.8 % of the total number of operated patients) underwent repeated laparoscopic pyeloplasty. Duration stay after primary laparoscopic pyeloplasty was from 3 to 5 days, on average (3.9±0.7) days. Postoperative period after secondary pyeloplasty was without complications, the bed-day was from 3 to 6 days, on average (4.3±0.6) days.CONCLUSION. Our opinion is that the optimal method for surgical treatment of patients with primary and secondary strictures of the pyeloureteral segment is laparoscopic pyeloplasty. This kind of surgery has a favorable security profile and optimal postoperative results. Considering the possible causes of relapse of the stricture of the pyeloureteral segment, we came to the conclusion that the frequency of relapse is mainly connected with selected suture material, which determines the severity of scar changes.